Online Language Phenomena in Modern Mandarin: A Linguistic Study of Popular Expressions and Digital Neologisms - Alindra, Devi Alvionita; Siregar, Feby Yoana; Siregar, Dina Shabrina Putri (TALENTA, 2026)
The rapid growth of digital technology and social media has significantly transformed global communication, including the use of Mandarin. Platforms WeChat, Douyin, and TikTok have accelerated linguistic change and fostered the emergence of Mandarin internet language. This study examines its main linguistic characteristics, formation processes, sociocultural drivers, and implications for academic, social, media, and educational contexts. Using a descriptive qualitative approach, data were collected from the three platforms and analyzed through phonological, morphological, semantic, pragmatic, and sociolinguistic perspectives. The findings reveal distinctive features such as pinyin-based abbreviations, numerical homophones, phonological wordplay, morphological innovation, and expressive hyperbole. Digital neologisms are shaped by linguistic mechanisms, meme culture, and social media virality, while their rapid spread is influenced by youth dominance, social competition, globalization, and online community identity. The study concludes that Mandarin internet language represents a natural linguistic evolution rather than degradation, reflecting cultural, technological, and generational changes in contemporary China.